The Spectator, 2002-03-14 - Spectator, Valdosta State University (Valdosta State University, 2002)
The Spectator, March 14, 2002. Pre-print Draft. Vol.70 no.09. Typical student female -- Center nearly finished -- VSU called to serve -- Farber Health Center earns high marks -- VSU retention high.
The Spectator: The Unfiltered, Uncensored Voice of the Students
Born digital draft copy. Converted from QuarkXpress format to PDF. Some content may be incomplete from final print editions. Some fonts have been changed.
Keywords: Valdosta State University -- Periodicals